Güncel Üroloji Çalışmaları VI - Ürolojik Aciller-Güz - Arslan, Ahmet Mervan; Hasırcı, Eray; Cincorop, Serdar; Çolak, Fatih; Perolli, Nijazi; Akça, Görkem; Orman, Erdem; Demir, Murat; Yazar, Selim; Dil, Eyüp; Bulut, Ender Cem; Kaba, Mustafa (2024)
-